Investment, Debt Instruments and Economic Growth: Their Impact on the Unemployment Rate of OIC Countries in the Asian Region - Ahmada Khoirul Umam; Onny Herlambang Putra Wardhana (Journal of Islamic Economics Lariba, 2020)
This study aims to determine the effect of investment, total debt, net debt, and real GDP growth on unemployment rates in the Asian OIC countries. This research uses a quantitative method with panel data regression. By using common effect model, the results shows investment had a significant effect on reducing the unemployment rate, while the total debt, net debt, and real GDP growth variables had no significant effect.